Opportunities and challenges toward developing an integrated anemia prevention and control programme Insights from two Philippine provinces. - Tuazon, M. A. G. (Compendium of Human Ecology Researches in the Philippines, 2003)
This study aimed to identify opportunities and challenges for planning and implementing an integrated plan for anemia prevention and control for the provinces of Eastern Samar and Isabela. Standard interventions (iron supplementation, food-based approaches such as food production, food fortification, dietary diversification, and public health measures) exist in the provinces. However, these are not implemented in an integrated manner. The opportunities include the presence of health and nutrition workers who can implement an integrated program on anemia, local chief executives who have positive views on health programs in general, and continuing demand from target groups for services to prevent and control anemia. However, the challenges include low awareness and utilization of services among target beneficiaries, which in turn can explain poor compliance to the iron supplementation regimen; low knowledge on planning and implementing interventions particularly targeting the most at-risk groups and selecting interventions among service providers; and existence of several monitoring and evaluation systems on nutrition and health which adds to the confusion in feedbacking. Existing interventions and commodities at the provincial level are insufficient to address anemia. There is no need for new interventions but integration of interventions into one program and incorporating creative and innovative strategies to increase consumer utilization and satisfaction are necessary. To ensure sustainability, stakeholders' cooperation and support of the LEs are similarly critical.